Pollen record and paleoenvironment of a 4210 years B.P.old sediment in the Bay of Guanabara, Rio de Janeiro, Brazil - Barth,Ortrud M. (2004)
Pollen analysis of a sediment sample obtained at 222 cm from the top of a drilling core collected in the Bay of Guanabara, Rio de Janeiro, was used as a tool to obtain more knowledge about pre-historical human living and environment. 14C datation revealed the age of 4210 years B.P. Most frequent pollen grains came from plants like Alchornea (Euphorbiaceae), Celtis (Ulmaceae), Lecythidaceae, Meliaceae, Ochnaceae and spores from forest Pteridophyta. Palynology and environmental studies revealed that agricultural activities could not be detected. The dense tropical rain forest was the dominant vegetation occurring in this region.